2021
DOI: 10.1136/bmjopen-2020-046263
|View full text |Cite
|
Sign up to set email alerts
|

‘Making the most of our situation’: a qualitative study reporting health providers’ perspectives on the challenges of implementing the prevention of mother-to-child transmission of HIV services in Lagos, Nigeria

Abstract: ObjectivesTo investigate the challenges of, and opportunities for, effective delivery of prevention of mother-to-child transmission (PMTCT) services from the perspectives of primary healthcare providers in Lagos, Nigeria.DesignThis qualitative study consisted of nine focus groups with 59 health providers, analysed thematically.SettingThirty-eight primary health facilities in central and western districts of Lagos, Nigeria.ParticipantsParticipants included nurses, nursing assistants, community health workers, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…This finding corresponds with a qualitative study in a similar setting where the fear of disclosure among HIV-positive women was influenced by their economic dependency on men, among other factors. 26 A previous study identified the largest barrier to spousal disclosure, which was fear of negative outcomes, especially divorce. Disclosure is a process that requires preparedness and time, as described in the process-oriented framework or disclosure processes model.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corresponds with a qualitative study in a similar setting where the fear of disclosure among HIV-positive women was influenced by their economic dependency on men, among other factors. 26 A previous study identified the largest barrier to spousal disclosure, which was fear of negative outcomes, especially divorce. Disclosure is a process that requires preparedness and time, as described in the process-oriented framework or disclosure processes model.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection process was carefully undertaken to ensure the quality of the data, and we ensured that data collectors who were selected had prior data collection experience. Prior to data collection, a pre-test was administered to ten (10) ART patients in the Asunafo North Municipal on populations that were similar. Throughout the whole data collection period, the investigators conducted intensive supervision on a daily basis.…”
Section: Quality Controlmentioning
confidence: 99%
“…Additionally, it was discovered that patients in Lagos, Nigeria, provided false contact details out of a refusal to accept HIV-positive results and to enrol in treatment, as well as a fear of stigma associated with the virus [10]. In Ghana, not much research has been conducted to investigate the precise causes of HIV patient loss from antiretroviral therapy (ART), particularly in the Asunafo South District of the Ahafo Region.…”
Section: Introductionmentioning
confidence: 99%
“…These collaborations are essential to address the multifaceted challenges and harness the opportunities for effective delivery of healthcare services, particularly in preventing mother-to-child transmission (PMTCT) of diseases like HIV. A qualitative study conducted in Lagos, Nigeria, investigated the challenges and opportunities for effective delivery of PMTCT services from the perspectives of primary healthcare providers (Kram et al, 2021). The study highlighted the importance of addressing patient-and health system-level challenges to improve PMTCT service delivery.…”
Section: Partnerships With Healthcare Providers and Institutionsmentioning
confidence: 99%
“…To address these challenges, providers suggested the provision of adequate supplies and training of healthcare workers. Additionally, to mitigate stigmatization, participants recommended home-based care, collaboration with traditional birth attendants and religious institutions, and designating an HIV health educator for each neighborhood (Kram et al, 2021).…”
Section: Partnerships With Healthcare Providers and Institutionsmentioning
confidence: 99%